Impact of Deactivated Mine Waste Substrates on the Growth and Cu, As and Pb Accumulation in Tubers, Roots, Stems and Leaves of Three Solanum tuberosum L. Varieties - Ana R. F. Coelho; Manuela Simões; Fernando H. Reboredo; José Almeida; Joaquim Cawina; Fernando Lidon (Plants)
Potato (Solanum tuberosum L.) is the world’s third most popular vegetable in terms of consumption and the fourth most produced. Potatoes can be easily cultivated in different climates and locations around the globe and often in soils contaminated by heavy metals due to industrial activities. This study assessed heavy metal accumulation in different organs of three S. tuberosum L. varieties (Agria, Désirée, and Red Lady) grown in different substrate formulations containing slag and waste from the Caveira polymetallic sulfite mine in Portugal. Results reveal that Cu, Pb, and As accumulation in the different organs of the plant depends on variety and substrate formulation, with tubers exceeding reference values from the literature. Tubers accumulated less Cu (varying between 17.3 and 32 mg/kg), Pb (varying between 5 and 27.6 mg/kg) and As (varying between 4 and 14.8 mg/kg) compared to other plant organs, and the Désirée variety exhibited high Pb (with a maximum of 27.6 mg/kg) accumulation in tubers compared to the remaining varieties. Although the phenological development of plants was not impacted, substrate formulation played a critical role in the plant’s metal uptake. The Agria variety presented a lower contamination risk in tubers, but potato cultivation in contaminated soils can present a risk to human health.